Optimizing ALT flap harvest: the role of combined preoperative duplex ultrasound and intraoperative ICG angiography for perforator selection - Thomas, Benjamin; Falkner, Florian; Didzun, Oliver; Panayi, Adriana C.; Ghanad, Iman; Hundeshagen, Gabriel; Gazyakan, Emre; Kneser, Ulrich; Bigdeli, Amir Khosrow (Life, 2025)
Planning and harvesting anterolateral thigh flaps (ALT) requires precise perforator selection and accurate tissue perfusion assessment.
Gesehen am 21.10.2025